2021
DOI: 10.3390/genes12111746
|View full text |Cite
|
Sign up to set email alerts
|

Translating the Role of mTOR- and RAS-Associated Signalopathies in Autism Spectrum Disorder: Models, Mechanisms and Treatment

Abstract: Mutations affecting mTOR or RAS signaling underlie defined syndromes (the so-called mTORopathies and RASopathies) with high risk for Autism Spectrum Disorder (ASD). These syndromes show a broad variety of somatic phenotypes including cancers, skin abnormalities, heart disease and facial dysmorphisms. Less well studied are the neuropsychiatric symptoms such as ASD. Here, we assess the relevance of these signalopathies in ASD reviewing genetic, human cell model, rodent studies and clinical trials. We conclude th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 194 publications
(239 reference statements)
1
10
0
1
Order By: Relevance
“…Indeed, the earlier the expression, the greater the clinical intersection between ASD and developmental delay [ 19 ]. Similar findings were highlighted by Vasic et al, providing a rationale for the importance of timing interventions early in development [ 20 ]. These and other studies suggest that many of the synaptic genes found to be associated with ASD are expressed prenatally and throughout early development, spatially and temporally coinciding with synaptic organization in brain regions relevant for ASD.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…Indeed, the earlier the expression, the greater the clinical intersection between ASD and developmental delay [ 19 ]. Similar findings were highlighted by Vasic et al, providing a rationale for the importance of timing interventions early in development [ 20 ]. These and other studies suggest that many of the synaptic genes found to be associated with ASD are expressed prenatally and throughout early development, spatially and temporally coinciding with synaptic organization in brain regions relevant for ASD.…”
supporting
confidence: 84%
“…One of these convergent pathways, indicated by the involvement of several genes in which pathogenic variants can increase the probability of ASD, is synaptic function: this pathway has been discussed in several contributions present in this Special Issue. For example, Vasic et al [ 20 ]. discuss the connections between observations in humans and those derived from murine studies of genes involved in so-called “signalopathies”, including PTEN , TSC1 , TSC2 and NF1 , and how their point of convergence is abnormal synaptic function [ 20 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A promising approach in delineating the functional consequences of genetic risk factors aims to study molecular or neural mechanisms, which show overlapping characteristics between species. For example, the role of mutations in the mTOR or RAS signalling pathways show similar neuropathological characteristics in human and rodent models [ 16 ]. Gene expression pattern, neural synaptic function, or the imbalance of inhibitory and excitatory neural functions are other well-studied aspects which can be compared between rodent and human models [ 13 , 17 , 18 ].…”
Section: Joint Mechanisms Across Modelsmentioning
confidence: 99%